Synthesis and Antimicrobial Activity of 2-(Substituted phenyl)-5-carboxy methyl-4-thiozolidinone Derivatives of Pyrimidine Benzene Sulfanamide (Sulphadiazine) - RAO, N. SRINIVASA; RAO, J.T. (Asian Journal of Chemistry, 2010)
Pyrimidine benzenes sulfanamide (sulphadiazine) has been synthesized by condensing with various aromatic aldehydes with thiomalic acid. All the compounds have been screened for their antimicrobial activity.